2010
DOI: 10.1007/s11547-010-0518-z
|View full text |Cite
|
Sign up to set email alerts
|

Role of sonoelastography in characterising breast nodules. Preliminary experience with 120 lesions

Abstract: The use of sonoelastography to complement mammography and ultrasonography could help in the differential diagnosis of nodular breast lesions, especially in Breast Imaging Reporting Data System (BI-RADS) 3 lesions with marked elasticity (S

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 21 publications
1
30
1
2
Order By: Relevance
“…In this study, the au- thors have concluded that elastography can increase the specificity of conventional ultrasonography up to 88.7%, especially in non-palpable lesions. Although some studies did not detect an improvement in specificity with the addition of US elastography (14,17), a number of other studies showed an increase in specificity (6-13). Cho et al (10) studied 100 non-palpable breast lesions and found the sensitivity as 82% and the specificity as 84%, and concluded that there were no significant differences between conventional US and elastography in the evaluation of solid breast masses.…”
Section: Discussionmentioning
confidence: 97%
“…In this study, the au- thors have concluded that elastography can increase the specificity of conventional ultrasonography up to 88.7%, especially in non-palpable lesions. Although some studies did not detect an improvement in specificity with the addition of US elastography (14,17), a number of other studies showed an increase in specificity (6-13). Cho et al (10) studied 100 non-palpable breast lesions and found the sensitivity as 82% and the specificity as 84%, and concluded that there were no significant differences between conventional US and elastography in the evaluation of solid breast masses.…”
Section: Discussionmentioning
confidence: 97%
“…The diagnostic accuracy of elasticity scoring has already been investigated in several previous studies [2,3,5, and a previous meta-analysis [37]. Our prior meta-analysis has shown a sensitivity of 79% and a specificity of 89% for use of ES in differentiating benign and malignant lesions [38].…”
Section: Introductionmentioning
confidence: 86%
“…Elasticity is the tendency of a tissue to resume the original size and shape; while strain is the level of change in size or shape in response to external compression (stress) [4]. Each pixel of the image is assigned one of 256 specific colors and demonstrates the magnitude of tissue strain depending on physiological and pathological changes in breast structure [3,5]. Harder tissues such as malignancy may result in decreased strain and are shown in blue, while softer tissues will reflect increased strain and are shown in red [3].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, new radiological imaging methods such as Elastography have been described about diagnosis of malign tissue. In previous studies (about prostate and breast cancer) it has been reported that stiffness grade of tumor tissue higher than in normal tissue by Elastographic examination (6,7,8). Aigner et al (3) performed testicular Elastography for 50 patients who have TLs detected with gray-scale US.…”
Section: Discussionmentioning
confidence: 99%
“…Elastography is a new sonographic method that directly discloses the elasticity features of the tissue and allows examination of changes in tissue hardness (4). Elastography has been proposed with promising results for differentiating benign from malignant lesions in some tissues, such as testis (4,5,6,7,8). Due to increasing stiffness of a mass, the risk of malignancy becomes higher and more sensitive to elasticity evaluation than palpation might obtain with recent sonographic devices (5).…”
Section: Introductionmentioning
confidence: 99%